The role of oil prices in Norwegian petroleum investments: An empirical study - Julia Skretting (Statistics Norway, Research Department, 2024)
This paper provides evidence that oil price fluctuations have been an important driver of petroleum investment in Norway. To show this, I utilize a Bayesian vector autoregressive (BVAR) model combined with local projections, using various investment data from national accounts and firms' survey data. I find that a 10 percent increase in real oil prices typically results in about a 4 percent rise in petroleum investment, primarily boosting activities in exploration and existing fields, while field development investments show minimal response. These results contribute to a broader understanding of the role of oil prices in shaping Norwegian business cycles.
Keywords: Q43; E22; C32; L71; 330; Oil Prices; VAR model; Investment Dynamics; Macroeconomic Shocks; Bayesian Analysis; Energy Economic